The nuclear barons. - Pringle, P., Spigelman, J. (New York Holt, Rinehart and Winston, 1981)
Discusses how the worlds destiny is controlled by a small group of scientists, businessmen, politicians, and military officers whose decisions on nuclear power have caused the present nuclear nightmare
Keywords: Fiction